Case Report: An EGFR-Targeted 4-1BB-agonistic Trimerbody Does Not Induce Hepatotoxicity in Transgenic Mice With Liver Expression of Human EGFR - Compte, Marta; Harwood, Seandean L.; Martínez-Torrecuadrada, Jorge; Perez-Chacon, Gema; González-García, Patricia; Tapia-Galisteo, Antonio; Van Bergen en Henegouwen, Paul M. P.; Sánchez, Aránzazu; Fabregat, Isabel; Sanz, Laura; Zapata, Juan M.; Alvarez-Vallina, Luis (Frontiers in Immunology, 2021)
Agonistic monoclonal antibodies (mAbs) targeting the co-stimulatory receptor 4-1BB are among the most effective immunotherapeutic agents across pre-clinical cancer models. However, clinical development of full-length 4-1BB agonistic mAbs, has been hampered by dose-limiting liver toxicity. We have previously developed an EGFR-targeted 4-1BB-agonistic trimerbody (1D8N/CEGa1) that induces potent anti-tumor immunity without systemic toxicity, in immunocompetent mice bearing murine colorectal carcinoma cells expressing human EGFR. Here, we study the impact of human EGFR expression on mouse liver in the toxicity profile of 1D8N/CEGa1. Systemic administration of IgG-based anti-4-1BB agonist resulted in nonspecific immune stimulation and hepatotoxicity in a liver-specific human EGFR-transgenic immunocompetent mouse, whereas in 1D8N/CEGa1-treated mice no such immune-related adverse effects were observed. Collectively, these data support the role of FcγR interactions in the major off-tumor toxicities associated with IgG-based 4-1BB agonists and further validate the safety profile of EGFR-targeted Fc-less 4-1BB-agonistic trimerbodies in systemic cancer immunotherapy protocols.